Dampak Senam Lansia terhadap Activity of Daily Living di Panti Sosial - Akhmad Yanuar Fahmi Pamungkas; Desi Trianita; Tri indah Wahyuni (Bali Medika Jurnal, 2025)
Penelitian ini bertujuan untuk mengevaluasi efek senam lansia terhadap Activity of Daily Living (ADL) pada lansia di UPT Pelayanan Sosial Tresna Werdha Glenmore Banyuwangi. Dengan menggunakan desain pretest-posttest satu kelompok, 52 lansia diikutsertakan dalam penelitian ini. Instrumen yang digunakan adalah Barthel Index untuk mengukur kemampuan ADL sebelum dan setelah intervensi senam lansia. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam kemandirian ADL, dengan 90,4% responden menjadi mandiri setelah mengikuti senam lansia, dibandingkan hanya 71,2% sebelum intervensi. Uji Wilcoxon menunjukkan nilai p = 0,002 (p < 0,05), mengindikasikan pengaruh positif yang signifikan. Temuan ini menunjukkan bahwa senam lansia dapat meningkatkan kemandirian lansia dalam melakukan aktivitas sehari-hari. Penelitian ini memberikan kontribusi pada pengembangan program senam yang dapat diimplementasikan di panti sosial, dengan dampak positif pada kualitas hidup lansia. Penelitian selanjutnya disarankan untuk mengeksplorasi dampak jangka panjang dan faktor-faktor lain yang mempengaruhi kemandirian lansia.   Video is a type of audiovisual media that is effectively used for mass, individual and group learning processes. It is hoped that this sleep training video can help parents understand and assist in implementing sleep training which is useful for training children's independence from an early age and reducing the risk of SIDS in infants. To determine the effectiveness of sleep training videos on parents' knowledge and attitude in implementing sleep training for infants 4-6 months in Darmasaba Village.This study employed pre-experimental study with one group pre-test and post-test design. It was conducted in Darmasaba Village from August-September 2023 and there were 25 parents recruited as the sample through total sampling technique. The results of the analysis level of knowledge and attitude using the Wilcoxon Rank Test showed that the P value was <0.05; thus, Ha was accepted. It can be concluded that the sleep training video is effective in increasing parents' knowledge and attitude in implementing sleep training for infants 4-6 months in Darmasaba Village.The results of the study show that sleep training videos are effective in increasing parents' knowledge and attitude in implementing sleep training for infants 4-6 months. There was an increase in knowledge and attitude regarding sleep training among parents after providing sleep training videos. However, parents tended to not be willing to implement sleep training because they were worried of the age was too early to carry out sleep training on infants.